Negative Kausalität - Birnbacher, Dieter (Ideen & Argumente., 2012)
The term "negative causality" denotes a highly controversial problem in metaphysics: Can negative entities such as the absence or the non-occurrence of certain events be causes or causal factors? This question is situated at the intersection of a series of fundamental questions that transcend disciplinary boundaries, questions concerning not only the nature of causality, actions, and events, but also the relationship between causality and moral and legal responsibility. This book is intended for philosophers, legal theorists, and theorists of science.